Design of Learning Trajectory on Number Patterns Using the Context of Aur Lake Tourism for Junior High School Students - Elly, As; Zulkardi, Zulkardi; Putri, Ratu Ilma Indra; Susanti, Ely; Mulyono, Budi (Mimbar Sekolah Dasar, 2025)
Number patterns are a mathematical topic that connects arithmetic and algebra while strengthening students’ mathematical reasoning foundations. Therefore, the teaching of this topic needs to be designed in a meaningful way. This study aims to describe the learning design of number patterns based on Indonesian Realistic Mathematics Education (PMRI) using the context of Aur Lake tourism for Grade VIII students at SMP IT Al-Furqon Wonosari, Musi Rawas Regency. The research method employed was design research with a validation studies type, consisting of three stages: (1) preparing for the experiment, which included a literature review, discussions with teachers, and the development of a Hypothetical Learning Trajectory (HLT); (2) the design experiment, which involved a piloting experiment and a teaching experiment; and (3) the retrospective analysis. The research subjects were Grade VIII students at SMP IT Al-Furqon Wonosari, with six students participating in the piloting experiment and twenty-three students in the teaching experiment. Data collection techniques included observation, interviews, documentation/video recordings, and student activity sheets. The collected data were analyzed using qualitative descriptive techniques. The results of this study produced a learning design for number patterns based on PMRI using the Aur Lake context, which can guide students in understanding and generalizing number patterns.